Apollo's arrow : the profound and enduring impact of coronavirus on the way we live - Christakis, Nicholas A. (New York : Little, Brown and Company, 2020)
"Apollo's Arrow offers a riveting account of the impact of the coronavirus pandemic as it swept through American society in 2020, and insight into how the recovery will unfold in the coming years. Drawing on momentous (yet dimly remembered) historical epidemics, contemporary analyses, and cutting-edge research from a range of scientific disciplines, the physician, sociologist, public health expert, and bestselling author Nicholas A. Christakis explores what it means to live in a time of plague--an experience that is paradoxically uncommon to the vast majority of humans who are alive, yet deeply fundamental to our species. Unleashing new divisions in our society as well as opportunities for cooperation, this twenty-first-century pandemic has upended our lives in ways that will test, but not vanquish, our already frayed collective culture. Featuring new, provocative arguments, a preface and afterword new to this edition, and vivid examples ranging across medicine, history, sociology, epidemiology, data science, and genetics, Apollo's Arrow envisions what happens when the great force of a deadly germ meets the enduring reality of our evolved social nature." -- Page 4 of cover.
An infinitesimal thing -- An old enemy returns -- Pulling apart -- Grief, fear, and lies -- Us and them -- Banding together -- Things change -- How plagues end.
"Originally published in hardcover by Little, Brown Spark, October 2020"--Title page verso.
Include bibliographical references (pages [349]-381) and index.
Keywords: COVID-19 (Disease) -- Social aspects; COVID-19 (Disease) -- Psychological aspects; COVID-19 Pandemic, 2020- -- Social aspects -- United States; COVID-19 Pandemic, 2020- -- Economic aspects -- Great Britain; Social change; Epidemics -- Social aspects; COVID-19 -- Aspect social; COVID-19 -- Aspect psychologique; Pandemie de COVID-19, 2020- -- Aspect social -- Etats-Unis.; Pandemie de COVID-19, 2020- -- Aspect economique -- Grande-Bretagne.; Epidemics -- Social aspects; Economics; Social aspects; Social change